Biological activity of plant extracts from Mexican semi-desert to management of Fusarium oxysporum from tomato: Efectividad de extractos vegetales sobre Fusarium oxysporum - Tucuch-Pérez, Marco Antonio; Bojorquez-Vega, Jose Jesus; Arredondo-Valdes, Roberto; Hernández-Castillo, Francisco Daniel; Anguiano-Cabello, Julia Cecilia (Ecosistemas y Recursos Agropecuarios, 2021)
Fusarium oxysporum causes losses in tomato production, to control it are used chemical fungicides that affect the environment and cause resistance problems; so alternatives such as plant extracts have been developed. The objective of the present work was to evaluate the biological effectiveness of plant extracts from the mexican semi-desert against F. oxysporum under greenhouse conditions. The treatments were: T1 = A. lechuguilla leaf (250 mg L-1), T2 = C. illinoinensis husk (250 mg L-1), T3 = L. graveolens leaf (500 mg L-1), T4 = L. graveolens stem (125 mg L-1), T5 = chemical witness, T6 = absolute witness (inoculated) and T7 = control; the incidence and severity of the disease, and morphometric variables were evaluated. A decrease in the incidence and severity of the disease was observed with extracts of A. lechuguilla leaf and L. graveolens stem, also a higher development in morphometric parameters of the plants.